Hubungan Kebiasaan Sarapan dengan Status Gizi Siswa: Literature Review - Huwaidy, Alwan Hibban Al; Zuraida, Reni; Febriani, Wiwi (Medula, 2025)
Students are a very valuable asset for the future of the nation. Good nutritional status is essential to support student achievement. However, currently Indonesia is experiencing a double nutritional problem in the form of malnutrition and overnutrition at school age. In addition, there are still few students in Indonesia who are accustomed to having breakfast with quality food in the morning. One of the factors that influences students' nutritional status is breakfast habits. This study aims to determine the relationship between breakfast habits and students' nutritional status. The method used is a literature review of 13 journals or articles from the Google Scholar database related to the Relationship between Breakfast Habits and Students' Nutritional Status published from 2015 to 2025. The results of this study indicate that the 12 journals or articles reviewed have a significant relationship between breakfast habits and nutritional status in students. Students who are accustomed to having breakfast will find it easier to meet their daily nutritional needs so that their nutritional status tends to be normal. However, students who are not accustomed to having breakfast will miss the opportunity to meet 15-30% of their daily nutritional needs so that their nutritional status is lacking. In addition, students who do not have breakfast tend to consume excessive lunch and high calories during the day so that their nutritional status is more. The conclusion of this study is that there is a relationship between breakfast habits and nutritional status in students.